DETERMINING THE CORRELATION BETWEEN THE PRIVACY CONSCIOUSNESS OF MIDWIFERY AND NURSING STUDENTS AND THEIR ATTITUDES TOWARD THE RECORDING AND PROTECTION OF PERSONAL HEALTH DATA - Durmus Iskender, Mahinur; Durmuş, Ayşenur (Iktisadi Kalkinma ve Sosyal Arastirmalar Dernegi, 2022)
Midwifery and nurses are to obey specific ethical principles when realizing their professional practice. One of these ethical principles is the principle of privacy and secrecy. This research aimed to determine the correlation between the privacy consciousness of midwifery and nursing students and their attitudes toward the recording and protection of personal health data. A descriptive and cross-sectional design was used. The study was conducted with 283 midwifery and nursing students in December 2021. A self-reported survey comprising the Demographic Information Form”, “The Privacy Consciousness Scale” and “The Attitude Toward the Recording and Protection of Personal Health Data Scale were distributed to midwifery and nursing students as a online-based survey. The students obtained a total of 3.81±0.95 points from the Attitude Toward the Recording and Protection of Personal Health Data Scale and a total of 4.30±0.77 points from the Privacy Consciousness Scale. It was determined a significant correlation between the privacy consciousness of midwifery and nursing students and the the Attitude Toward the Recording and Protection of Personal Health Data Scale in a positive direction. This study showed that as midwifery and nursing students’ privacy consciousness and attitudes toward the recording and protection of personal health data were determined to be high.
Keywords: 4. Education